KIDUNG RUMEKSO ING WENGI DAN KORELASINYA DENGAN SURAT MU’AWWIDHATAIN: Kajian Living Qur’an - Nafsiyah, Zakyyatun; Ansori, Ibnu Hajar (QOF, 2017)
This article is the result of a review of the correlation between Kidung Rumekso Ing Wengi with Surah Mu’awwidhatain based on its content of meaning and function. It can be concluded that Kidung Rumekso Ing Wengi has a close correlation with the Surah Mu’awwidhatain, which is a manifestation of the meaning of the word Qul which includes the value of Tawheed and the teaching of doing Tirakat in order to maximize the potential for self-protection from night, human, jin and satan and other creatures of God. The Song of Rumekso Ing Wengi is an early part of the song Fiber containing 41 stupas of Dhandhanggula’s electric, which illustrates the sweetness of the spiritual teaching. The forty-one verses are divided into four parts of the hymn. The first part is the first statue until the 10th is the Song of Rumekso Ing wengi or Kidung Sarira Ayu. The 11th to 24th Chapters are the Art of Songs. The next verse, which is the 25th to 35th is Kidung Jati Mulya, and the last part of the 36th to 41st stanza is the Song of Mar Marti. The Surah Mu’awwidhatain is the name of two Surahs that go hand in hand, namely al-Falaq and al-Na s. The name Mu’awwidhatain is derived from the word a’udhu which means I seek refuge, so Mu’awwidhatain means two Surahs that guide the reader to the shelter, or put it into a protected arena.